2020
DOI: 10.5080/u25205
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Findings in Cannabis Users

Abstract: Kannabis kullanımının retina sinir lifi tabakası (RSLT) ve maküler ganglion hücre-iç pleksiform tabaka (MGH-İPT) üzerine olan yapısal etkilerinin optik koherens tomografi ile değerlendirilmesi amaçlanmıştır. Yöntem: Bu prospektif, karşılaştırmalı çalışmaya Muş Devlet Hastanesi Psikiyatri Polikliniği'ne başvuran ve kannabis kullanımı mevcut olan 26 kişi ile bu kişilerle yaş ve cinsiyet açısından uyumlu 27 sağlıklı gönüllü dâhil edilmiştir. Her iki gruba optik koherens tomografi (OKT) çekimi uygulanmıştır. OKT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Orum et al found that patients with alcohol use show decrease in retinal fiber layers in comparison to non-alcoholic, and this decrease is associated with duration of alcohol use [35]. Similar thinning of the RNFL layers were reported in cocaine and cannabis users [38,40].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Orum et al found that patients with alcohol use show decrease in retinal fiber layers in comparison to non-alcoholic, and this decrease is associated with duration of alcohol use [35]. Similar thinning of the RNFL layers were reported in cocaine and cannabis users [38,40].…”
Section: Introductionmentioning
confidence: 72%
“…Kalenderoglu and Orum [32] found that RNFL thickness increased in patients with cannabis use and patients with multiple substance use compared to healthy controls. In contrast, another study reported decreased RNFL thickness in cannabis users [40]. Another study included patients with alcohol and tobacco dependency who had thinning in all quadrants of RNFL [37].…”
Section: Discussionmentioning
confidence: 96%
“…The present study chose to use only the results of right eye for further analysis to decrease the complexity of the tables. Although there are some studies in which only one eye was selected 22 , 37 both eyes should be scanned, especially in the context of the brain asymmetry hypothesis in psychotic disorders. Besides, there can be differences between left and right eyes as it relates to retinal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Then, OCT studies were conducted to investigate the etiology of bipolar disorder (BD), major depression (MD), obsessive-compulsive disorder (OCD), and even substance use disorders. 14,[17][18][19] Findings such as the presence of structural brain abnormalities that could be observed in both acute and remission stages of bipolar disorder (BD), structural cranial abnormalities during the first attack, and a progressive decrease in the total brain gray matter volume could be a sign of progressive neurodegeneration. 20 These findings led to a focus on retinal neural networks in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 The findings of the rapidly increasing studies demonstrated that retinal examination with OCT could be a valid, easily accessible, and non-invasive method to investigate brain pathology in neuropsychiatric disorders. 8,[17][18][19][20][21][22] Additionally, since it does not technically involve a closed area like CT or MR imaging, it may play a role in facilitating patient compliance in GAD, which is often accompanied by panic attacks and claustrophobia.…”
Section: Introductionmentioning
confidence: 99%